Analisa Pengaruh Penambahan Cangkang Kerang Terhadap Sifat Mekanik Material Komposit Berpenguat Serat Pinang - Saputra, I Nyoman Ardika; Sudia, Budiman; Aksar, Prinob (Enthalpy : Jurnal Ilmiah Mahasiswa Teknik Mesin, 2024)
Composite materials reinforced with natural fibers continue to be developed as alternative materials to replace composite materials. The purpose of this study was to determine the effect of the composition of the matrix, fiber and pokea shell filler on the tensile strength value of the composite polyester resin reinforced with areca nut shell fiber; To determine the effect of the composition of the matrix, fiber and pokea shell filler on the bending strength value of the composite polyester resin reinforced with areca nut shell fiber. Using the Hand Lay Up method, areca nut skin fiber and pokea shell powder filler. Using tensile and bending testing. The results of this study show that the highest average tensile stress is the fraction 70%:20%:10%, the average tensile stress is 13,752 MPa given a force of 1143,687 N. The lowest composite average tensile stress value is the fraction. 70:5%:25% indicates 7,745 MPa. The highest bending test value in the 70%:5%:25% fraction is 35,981 MPa which is given a force of 357,883 N and the lowest average bending stress value is in the 70%:20%:10% fraction of 31,777 MPa given a force of 365,377 N. Keywords: Composite, tensile strength, ultimate strength, fiber